2015
DOI: 10.1111/mec.13219
|View full text |Cite
|
Sign up to set email alerts
|

Applying ecological models to communities of genetic elements: the case of neutral theory

Abstract: A promising recent development in molecular biology involves viewing the genome as a miniecosystem, where genetic elements are compared to organisms and the surrounding cellular and genomic structures are regarded as the local environment. Here we critically evaluate the prospects of Ecological Neutral Theory (ENT), a popular model in ecology, as it applies at the genomic level. This assessment requires an overview of the controversy surrounding neutral models in community ecology. In particular, we discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…It has been recently suggested that the relationships between genome components (including genes, transposable elements, or any sequence able to persist over evolutionary time) were similar to the relationships between individuals or species in ecosystems (10,49,50), although the possibility to apply ecological formalism to genome evolution remains questionable (51). Here, we brought substantial evidence that the relationships between autonomous and nonautonomous mariner TE copies were analogous to parasitism: Mos1 copies (the "hosts") are able to survive and replicate by themselves, whereas peach copies (the "parasites") are unable to transpose without Mos1 copies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently suggested that the relationships between genome components (including genes, transposable elements, or any sequence able to persist over evolutionary time) were similar to the relationships between individuals or species in ecosystems (10,49,50), although the possibility to apply ecological formalism to genome evolution remains questionable (51). Here, we brought substantial evidence that the relationships between autonomous and nonautonomous mariner TE copies were analogous to parasitism: Mos1 copies (the "hosts") are able to survive and replicate by themselves, whereas peach copies (the "parasites") are unable to transpose without Mos1 copies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this conflict, many genomes are littered with a bulk of TE-derived DNA that is often relatively transcriptionally and recombinationally inert (Fedoroff, 2012). But while this conflict between TEs and their host has long been noted to shape general patterns of TE evolution (Charlesworth and Charlesworth, 1983;Charlesworth and Langley, 1989;Kidwell and Lisch, 1997;Venner et al, 2009), the details of how this conflict unfolds are tenuous and rarely well understood (Linquist et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…genome size evolution | DNA loss | transposable elements | amniotes | flight T he nature and relative importance of the molecular mechanisms and evolutionary forces underlying genome size variation has been the subject of intense research and debate (1)(2)(3)(4)(5)(6)(7). Variation in genome sizes may not always occur at a level where natural selection is strong enough to prevent genetic drift to determine their fate (neutral or effectively neutral variation) (3).…”
mentioning
confidence: 99%